MENINGKATKAN PEMBELAJARAN MEMBACA KRITIS MAHASISWA TERHADAP PENGEMBANGAN KETERAMPILAN INDIVIDU MELALUI SQ3R - Fadhilatul Ilmah; Aguwin Tarissa Putri; Arindra Dwi Mahesta; Lutfi Ana Amalia (Jurnal Praksis dan Dedikasi Sosial (JPDS), 2023)
IMPROVING STUDENT CRITICAL READING LEARNING TOWARDS INDIVIDUAL SKILL DEVELOPMENT THROUGH SQ3RScience and technology are developing rapidly so that they affect college graduates. Mastery of science and technology is needed so that graduates are able to compete in the world of work. Education plays an important role in forming quality human beings with the aim of being able to follow the development of science and technology. Education emphasizes both cognitive and non-cognitive aspects as critical thinking skills. By thinking critically, individuals will be able to make decisions to be taken, be open to differences of opinion, and be able to know and differentiate the reasons why other people have different decisions and opinions. For this reason, researchers have efforts to improve students' critical reading learning, towards the development of individual skills through SQ3R (survey, question, read, recite, review). The purpose of this research is to find out about SQ3R, develop critical reading skills, and the relationship between SQ3R and critical reading for individual skills. In this study using the literature review method, the source used is Google Scholar in the form of journals and articles. The results of the research are shown from the student learning outcomes that have been achieved through SQ3R, so that they are able to read critically.Ilmu pengetahuan serta teknologi berkembang cepat sehingga berpengaruh pada lulusan perguruan tinggi. Penguasaan ilmu pengetahuan dan teknologi sangat diperlukan agar lulusan mampu bersaing di dunia kerja. Pendidikan berperan penting dalam membentuk manusia yang berkualitas dengan tujuan mampu mengikuti perkembangan IPTEK. Pendidikan menekankan baik pada aspek kognitif maupun non kognitif sebagai kemampuan berpikir kritis. Dengan berpikir kritis individu akan mampu membuat keputusan yang akan diambil, terbuka dengan adanya perbedaan pendapat, serta bisa mengetahui serta membedakan alasan mengapa orang lain mempunyai keputusan dan pendapat yang berbeda. Untuk itu peneliti memiliki upaya meningkatkan pembelajaran membaca kritis pada mahasiswa, terhadap pengembangan keterampilan individu melalui SQ3R (survey, question, read, recite, review). Adanya penelitian ini memiliki tujuan untuk mengetahui tentang SQ3R, mengembangkan kemampuan membaca kritis, dan hubungan SQ3R dengan membaca kritis untuk keterampilan individu. Dalam penelitian ini menggunakan metode literatur review, sumber yang digunakan yakni pada google scholar berupa jurnal dan artikel. Hasil penelitian ditunjukkan dari hasil belajar mahasiswa yang telah tercapai melalui SQ3R, sehingga mampu membaca kritis.